Representation of Political System in Song Lyrics of “Only The Young”: A John Fiske Semiotic Analysis - Bully, Nurlina Ahmad; Suherman, Ansar; Maulana, Harry Fajar (Jogjakarta Communication Conference (JCC), 2025)
This study shows the meaning of the political system in the lyrics of the song "Only the Young" using John Fiske's semiotic analysis as a novelty in research. This study uses a qualitative approach that aims to gain an understanding of human or social phenomena by providing an in-depth description that can be explained in words both natural phenomena and human engineering results. This study focuses on the meaning of signs in the text through three levels of semiotics from John fiske, namely the level of reality, the level of representation, and the level of ideology.